Młodzi polscy emigranci na globalnym rynku pracy. Migracyjne doświadczenia zawodowe w trzech perspektywach temporalnych - Kozielska, Joanna (My University, 2014)
A guarantee of the access to the European labour markets was a very important part of the Polish foreign policy during the negotiation of the conditions under which Poland became a member of the European Union. Nine years ago, at the time of Polish accession, the Poles as citizens of the European Union gained the right to undertake legal work in other Member States. This chance was used by the Polish young people – ”third generation migrants,” tempted by better earnings and prospects for the future. The text is an attempt to capture the reality of migration in the context of work. It also attempts to answer the question if the economic migration is the time that contributes to one’s professional career, experience and professional potential, and builds a choice-based and coherent professional career or if it is only the earning episode that does not contribute in any way to the professional career of a young person.
Keywords: Emigracja zarobkowa; deprecjacja kwalifikacji